Regional conservation genomics: insights and opportunities from northern Australia - Teigan Cremona; Brenton von Takach; Robyn Shaw; Alexander Carey; Bridget Campbell; Skye Cameron; Renee Catullo; Caroline Chong; Saul Cowen; Danielle Edwards; Emilie Ens; Tony Griffiths; et al. (Biodiversity and Conservation, 2025)
Biodiversity conservation in northern Australia is characterised by high endemism, data deficiency, and high Indigenous land tenure and population. The Northern Australia Conservation Genomics Forum brought together experts to explore current genetic research with particular emphasis on integration of genomics within conservation practices. We discuss the regional biodiversity of northern Australia, highlighting the unique biogeographic patterns, known and unknown species diversity, and ongoing threats such as habitat degradation, altered fire regimes, invasive species, and climate change. This article synthesises key themes from the forum, including the current application of genomics in conservation, gaps and areas of need and opportunity to advance species conservation in this sparsely populated, yet iconic region of Australia. We highlight the need to expand collaborative research partnerships across land tenures with Indigenous organisations, pastoralists, government and non-government organisations, which is crucial for the effective study and conservation of the region’s biodiversity. The paper identifies the challenges and opportunities in applying genomic data to conservation strategies and applied management, including species translocations and habitat management, while acknowledging the limitations and gaps in current research and collections. The insights from this forum emphasise the advantages in using genomics to inform conservation decisions, and the need for continued research and collaboration to protect northern Australia’s unique biodiversity.

Evaluation of three serological tests for the diagnosis of Brucella suis in dogs using Bayesian latent class analysis - Catherine C. Kneipp; Ronald Coilparampil; Mark Westman; Monica Suann; Jennifer Robson; Simon M. Firestone; Richard Malik; Siobhan M. Mor; Mark A. Stevenson; Anke K. Wiethoelter (Preventive Veterinary Medicine, 2024)

Large diversity in AMOC internal variability across NEMO-based climate models - Alcide Zhao; Jon Robson; Rowan Sutton; Michael W.K. Lai; Jennifer V. Mecking; Stephen Yeager; Tillys Petit (Climate Dynamics, 2024)
We characterise, and explore the drivers of, differences in the internal variability of the atlantic meridional overturning circulation (AMOC) across five NEMO-based CMIP6 class climate models. While the variability of AMOC variability is dominated by its lower dense limb in all models, there is large diversity in the timescale, multidecadal variability, and latitudinal coherence of AMOC across models. In particular, the UK models have much weaker AMOC multidecadal variability and latitudinal coherence. The model diversity is associated with differences in salinity-governed surface density variations which drive high-density water mass transformation (WMT) in the Greenland–Iceland–Norwegian Seas (GIN) and the Arctic. Specifically, GIN Seas WMT shows large multidecadal variability which has a major impact on AMOC variability in non-UK models. In contrast, the smaller variability in GIN Seas WMT in the UK models has limited impact on the lower latitude AMOC via the Denmark strait overflow mass transport. This leads to a latitudinally less coherent and weaker multidecadal variability of the AMOC lower limb. Such differences between UK and non-UK models are related to differences in model mean states and densification processes in the Arctic and GIN Seas. Consequently, we recommend further in-depth studies to better understand and constrain processes driving salinity changes in the Arctic and GIN Seas for more reliable representation of the AMOC in climate models.

Spatialization of Brazilian pig production: relationship between productive, physical, environmental, and socio-economic variables - Isabel C. M. da Silva; Bárbara Bremm; Jennifer L. Teixeira; Nathalia S. Costa; Júlio O.J. Barcellos; José Braccini; Robson J. Cesconeto; Concepta McManus (Tropical Animal Health and Production, 2017)

Differences in the distribution of synemin, paranemin, and plectin in skeletal muscles of wild-type and desmin knock-out mice - Lena Carlsson; Zhen Lin Li; Denise Paulin; Maureen G. Price; Jennifer Breckler; Richard M. Robson; Gerhard Wiche; Lars-Eric Thornell (Histochemistry and Cell Biology, 2000)

Rapid mapping of markers applying vectorette technology to YAC fragmentation allows easy assembly of a high-density STS bacterial clone contig spanning the markers D6S1260-D6S1918 - Jeremy D. Shearman; Jennifer J. Pointon; Alison T. Merryweather-Clarke; Caroline Stone; Sharon W. Horsley; Lyndal Kearney; William M. Rosenberg; Kathryn J. H. Robson (Mammalian Genome, 1998)